Categories: MCQ Questions

MCQ Questions for Class 10 Maths Quadratic Equations with Answers

Free PDF Download of CBSE Class 10 Maths Chapter 4 Quadratic Equations Multiple Choice Questions with Answers. MCQ Questions for Class 10 Maths with Answers was Prepared Based on Latest Exam Pattern. Students can solve NCERT Class 10 Maths Quadratic Equations MCQs with Answers to know their preparation level.

Class 10 Maths MCQs Chapter 4 Quadratic Equations

1. Which of the following is not a quadratic equation
(a) x² + 3x – 5 = 0
(b) x² + x3 + 2 = 0
(c) 3 + x + x² = 0
(d) x² – 9 = 0

Answer/Explanation

Answer: b
Explaination:Reason: Since it has degree 3.


2. The quadratic equation has degree
(a) 0
(b) 1
(c) 2
(d) 3

Answer/Explanation

Answer: c
Explaination:Reason: A quadratic equation has degree 2.


3. The cubic equation has degree
(a) 1
(b) 2
(c) 3
(d) 4

Answer/Explanation

Answer: c
Explaination:Reason: A cubic equation has degree 3.


4. A bi-quadratic equation has degree
(a) 1
(b) 2
(c) 3
(d) 4

Answer/Explanation

Answer: d
Explaination:Reason: A bi-quadratic equation has degree 4.


5. The polynomial equation x (x + 1) + 8 = (x + 2) {x – 2) is
(a) linear equation
(b) quadratic equation
(c) cubic equation
(d) bi-quadratic equation

Answer/Explanation

Answer: a
Explaination:Reason: We have x(x + 1) + 8 = (x + 2) (x – 2)
⇒ x² + x + 8 = x² – 4
⇒ x² + x + 8- x² + 4 = 0
⇒ x + 12 = 0, which is a linear equation.


6. The equation (x – 2)² + 1 = 2x – 3 is a
(a) linear equation
(b) quadratic equation
(c) cubic equation
(d) bi-quadratic equation

Answer/Explanation

Answer: b
Explaination:Reason: We have (x – 2)² + 1 = 2x – 3
⇒ x² + 4 – 2 × x × 2 + 1 = 2x – 3
⇒ x² – 4x + 5 – 2x + 3 = 0
∴ x² – 6x + 8 = 0, which is a quadratic equation.


7. The roots of the quadratic equation 6x² – x – 2 = 0 are

Answer/Explanation

Answer: c
Explaination:Reason: We have 6×2 – x – 2 = 0
⇒ 6x² + 3x-4x-2 = 0
⇒ 3x(2x + 1) -2(2x + 1) = 0
⇒ (2x + 1) (3x – 2) = 0
⇒ 2x + 1 = 0 or 3x – 2 = 0
∴ x =\(-\frac{1}{2}\), x = \(\frac{2}{3}\)


8. The quadratic equation whose roots are 1 and
(a) 2x² + x – 1 = 0
(b) 2x² – x – 1 = 0
(c) 2x² + x + 1 = 0
(d) 2x² – x + 1 = 0

Answer/Explanation

Answer: b
Explaination:Reason: Required quadratic equation is


9. The quadratic equation whose one rational root is 3 + √2 is
(a) x² – 7x + 5 = 0
(b) x² + 7x + 6 = 0
(c) x² – 7x + 6 = 0
(d) x² – 6x + 7 = 0

Answer/Explanation

Answer: d
Explaination:Reason: ∵ one root is 3 + √2
∴ other root is 3 – √2
∴ Sum of roots = 3 + √2 + 3 – √2 = 6
Product of roots = (3 + √2)(3 – √2) = (3)² – (√2)² = 9 – 2 = 7
∴ Required quadratic equation is x² – 6x + 7 = 0


10. The equation 2x² + kx + 3 = 0 has two equal roots, then the value of k is
(a) ±√6
(b) ± 4
(c) ±3√2
(d) ±2√6

Answer/Explanation

Answer: d
Explaination:Reason: Here a = 2, b = k, c = 3
Since the equation has two equal roots
∴ b² – 4AC = 0
⇒ (k)² – 4 × 2 × 3 = 0
⇒ k² = 24
⇒ k = ± √24
∴ k= ± \(\pm \sqrt{4 \times 6}\) = ± 2√6


11. The roots of the quadratic equation \(x+\frac{1}{x}=3\), x ≠ 0 are.

Answer/Explanation

Answer: c
Explaination:Reason: We have \(x+\frac{1}{x}=3\)
⇒ \(\frac{x^{2}+1}{x}=3\)
⇒ x² + 1 = 3x
On comparing with ax² + bx + c = 0
∴ a = 1, b = – 3, c = 1
⇒ D = b² – 4ac = (-3)² – 4 × (1) × (1) = 9 – 4 = 5


12. The roots of the quadratic equation 2x² – 2√2x + 1 = 0 are

Answer/Explanation

Answer: c
Explaination:Reason: Here a = 2, b = -2√2 , c = 1
∴ D = b² – 4ac = (-2√2 )² – 4 × 2 × 1 = 8 – 8 = 0


13. The sum of the roots of the quadratic equation 3×2 – 9x + 5 = 0 is
(a) 3
(b) 6
(c) -3
(d) 2

Answer/Explanation

Answer: c
Explaination:Reason: Here a = 3, b = -9, c = 5
∴ Sum of the roots \(=\frac{-b}{a}=-\frac{(-9)}{3}=3\)


14. If the roots of ax2 + bx + c = 0 are in the ratio m : n, then
(a) mna² = (m + n) c²
(b) mnb² = (m + n) ac
(c) mn b² = (m + n)² ac
(d) mnb² = (m – n)² ac

Answer/Explanation

Answer: c
Explaination:


15. If one root of the equation x² + px + 12 = 0 is 4, while the equation x² + px + q = 0 has equal roots, the value of q is

Answer/Explanation

Answer: a
Explaination:Reason: Since 4 is a root of x² + px + 12 = 0
∴ (4)² + p(4) + 12 = 0
⇒ p = -7
Also the roots of x² + px + q = 0 are equal, we have p² – 4 x 1 x q = 0
⇒ (-7)² -4q = 0
\(\therefore q=\frac{49}{4}\)


16. a and p are the roots of 4x² + 3x + 7 = 0, then the value of \(\frac{1}{\alpha}+\frac{1}{\beta}\) is

Answer/Explanation

Answer: b
Explaination:


17. If a, p are the roots of the equation (x – a) (x – b) + c = 0, then the roots of the equation (x – a) (x – P) = c are
(a) a, b
(b) a, c
(c) b, c
(d) none of these

Answer/Explanation

Answer: a
Explaination:Reason: By given condition, (x – a) (x – b) + c = (x – α) (x – β)
⇒ (x – α) (x – β) – c = (x – a) (x – b)
This shows that roots of (x – α) (x – β) – c are a and b


18. Mohan and Sohan solve an equation. In solving Mohan commits a mistake in constant term and finds the roots 8 and 2. Sohan commits a mistake in the coefficient of x. The correct roots are
(a) 9,1
(b) -9,1
(c) 9, -1
(d) -9, -1

Answer/Explanation

Answer: a
Explaination:Reason: Correct sum = 8 + 2 = 10 from Mohan
Correct product = -9 x -1 = 9 from Sohan
∴ x² – (10)x + 9 = 0
⇒ x² – 10x + 9 = 0
⇒ x² – 9x – x + 9
⇒ x(x – 9) – 1(x – 9) = 0
⇒ (x-9) (x-l) = 0 .
⇒ Correct roots are 9 and 1.


19. If a and p are the roots of the equation 2x² – 3x – 6 = 0. The equation whose roots are \(\frac{1}{\alpha}\) and \(\frac{1}{\beta}\) is
(a) 6x² – 3x + 2 = 0
(b) 6x² + 3x – 2 = 0
(c) 6x² – 3x – 2 = 0
(d) x² + 3x-2 = 0

Answer/Explanation

Answer: b
Explaination:


20. If the roots of px2 + qx + 2 = 0 are reciprocal of each other, then
(a) P = 0
(b) p = -2
(c) p = ±2
(d) p = 2

Answer/Explanation

Answer: d
Explaination:Reason: here α = \(\frac{1}{β}\)
∴ αβ = 1
⇒ \(\frac{2}{p}\) = 1
∴ p = 2


21. If one root of the quadratic equation 2x² + kx – 6 = 0 is 2, the value of k is
(a) 1
(b) -1
(c) 2
(d) -2

Answer/Explanation

Answer: b
Explaination:Reason: Scice x = 2 is a root of the equation 2x² + kx -6 = 0
∴ 2(2)² +k(2) – 6 = 0
⇒ 8 + 2k – 6 = 0
⇒ 2k = -2
∴ k = -1


22. The roots of the quadratic equation

(a) a, b
(b) -a, b
(c) a, -b
(d) -a, -b

Answer/Explanation

Answer: d
Explaination:


23. The roots of the equation 7x² + x – 1 = 0 are
(a) real and distinct
(b) real and equal
(c) not real
(d) none of these

Answer/Explanation

Answer: a
Explaination:Reason: Here a = 2, b = 1, c = -1
∴ D = b² – 4ac = (1)² – 4 × 2 × (-1) = 1 + 8 = 9 > 0
∴ Roots of the given equation are real and distinct.


24. The equation 12x² + 4kx + 3 = 0 has real and equal roots, if
(a) k = ±3
(b) k = ±9
(c) k = 4
(d) k = ±2

Answer/Explanation

Answer: a
Explaination:Reason: Here a = 12, b = 4k, c = 3
Since the given equation has real and equal roots
∴ b² – 4ac = 0
⇒ (4k)² – 4 × 12 × 3 = 0
⇒ 16k² – 144 = 0
⇒ k² = 9
⇒ k = ±3


25. If -5 is a root of the quadratic equation 2x² + px – 15 = 0, then
(a) p = 3
(b) p = 5
(c) p = 7
(d) p = 1

Answer/Explanation

Answer: c
Explaination:Reason: Since – 5 is a root of the equation 2x² + px -15 = 0
∴ 2(-5)² + p (-5) – 15 = 0
⇒ 50 – 5p -15 = 0
⇒ 5p = 35
⇒ p = 7


26. If the roots of the equations ax² + 2bx + c = 0 and bx² – 2√ac x + b = 0 are simultaneously real, then
(a) b = ac
(b) b2 = ac
(c) a2 = be
(d) c2 = ab

Answer/Explanation

Answer: b
Explaination:Reason: Given equations have real roots, then
D1 ≥ 0 and D2 ≥ 0
(2b)² – 4ac > 0 and (-2√ac)² – 4b.b ≥ 0
4b² – 4ac ≥ 0 and 4ac – 4b2 > 0
b² ≥ ac and ac ≥ b²
⇒ b² = ac


27. The roots of the equation (b – c) x² + (c – a) x + (a – b) = 0 are equal, then
(a) 2a = b + c
(b) 2c = a + b
(c) b = a + c
(d) 2b = a + c

Answer/Explanation

Answer: d
Explaination:Reason: Since roots are equal
∴ D = 0 => b² – 4ac = 0
⇒ (c – a)² -4(b – c) (a – b) = 0
⇒ c² – b² – 2ac -4(ab -b² + bc) = 0 =>c + a-2b = 0 => c + a = 2b
⇒ c² + a² – 2ca – 4ab + 4b² + 4ac – 4bc = 0
⇒ c² + a² + 4b² + 2ca – 4ab – 4bc = 0
⇒ (c + a – 2b)² = 0
⇒ c + a – 2b = 0
⇒ c + a = 2b


28. A chess board contains 64 equal squares and the area of each square is 6.25 cm². A border round the board is 2 cm wide. The length of the side of the chess board is
(a) 8 cm
(b) 12 cm
(c) 24 cm
(d) 36 cm

Answer

Answer: c


29. One year ago, a man was 8 times as old as his son. Now his age is equal to the square of his son’s age. Their present ages are
(a) 7 years, 49 years
(b) 5 years, 25 years
(c) 1 years, 50 years
(d) 6 years, 49 years

Answer

Answer: a


30. The sum of the squares of two consecutive natural numbers is 313. The numbers are
(a) 12, 13
(b) 13,14
(c) 11,12
(d) 14,15

Answer

Answer: a


31. Which of the following is not a quadratic equation? [NCERT Exemplar Problems]
(a) 2(x – 1)² = 4x² – 2x + 1
(b) 2x – x² = x² + 5
(c) (√2x + √3 )² + x² = 3x² – 5x
(d) (x² + 2x)² = x4 + 3 + 4x3

Answer/Explanation

Answer: c
Explaination:
2x² + 3 + 2√6 x + x² = 3x² – 5x
2√6x + 5x + 3 = 0


32. If (x – a) is one of the factors of the polynomial ax² + bx + c, then one of the roots of ax² + bx + c = 0 is
(a) 1
(b) c
(c) a
(d) none of these

Answer/Explanation

Answer: c
Explaination:
∵ x – a is one of the factors one root = a.


33. Which of the following are the roots of the quadratic equation, x² – 9x + 20 = 0 by factorisation?
(a) 3, 4
(b) 4, 5
(c) 5, 6
(d) 6, 1

Answer/Explanation

Answer: b
Explaination:
Given equation is x² – 9x + 20 = 0
⇒ x² – 5x – 4x + 20 = 0
⇒ x(x – 5) – 4(x – 5) = 0
⇒ (x – 5) (x – 4) = 0
⇒ either x – 5 = 0 and x – 4 = 0
⇒ x = 5 and x = 4
∴ x = 4 and 5 are the roots/solution of the given quadratic equation.


34. If (1 – p) is a root of the equation x² + px + 1 -p = 0, then roots are
(a) 0, 1
(b) -1, 1
(c) 0, -1
(d) – 1, 2

Answer/Explanation

Answer: c
Explaination:
(1 -p) is a root
∴ (1 – p)² + p(1 – p)+ 1 – p = 0
⇒ (1 – p)[1 – p + p + 1] = 0
⇒ (1 – p)(2) = 0
⇒ p=1
x²+x = 0
One root = 0 and another root = – 1
∴ roots are 0 and – 1.


35. If a, P are roots of the equation x² + 5x + 5 = 0, then equation whose roots are a + 1 and p + 1 is
(a) x² + 5x – 5 = 0
(b) x² + 3x + 5 = 0
(c) x² + 3x + 1 = 0
(d) none of these

Answer/Explanation

Answer: c
Explaination:
α + β = -5, αβ = 5.
Required equation is x² – (α + 1 + β + 1)x + (α + 1) (β + 1) = 0
⇒ x² – (α + β + 2)x + (αβ + α + β +1) = 0
⇒ x² – (-5 + 2)x + (5 – 5 + 1) = 0
⇒ x² + 3x + 1 = 0


36. Which of the following equations has two distinct real roots? [NCERT Exemplar Problems]
(a) 2x² – 3√2x + \(\frac{9}{4}\) =0
(b) x² + x – 5 = 0
(c) x² + 3x + 2√2 = 0
(d) 5x² – 3x + 1 = 0

Answer/Explanation

Answer: b
Explaination: (b) D > 0


37. Which of the following equations has no real roots ? [NCERT Exemplar Problems]
(a) x² – 4x + 3√2 =0
(b) x² + 4x – 3√2 = 0
(c) x² – 4x – 3√2 = 0
(d) 3x² + 4√3x + 4 = 0

Answer/Explanation

Answer: a
Explaination: (a) D < 0


38. (x² + 1)² – x² = 0 has [NCERT Exemplar Problems]
(a) four real roots
(b) two real roots
(c) no real roots
(d) one real root

Answer/Explanation

Answer: c
Explaination: (c) no real roots


39. If the difference of the roots of the equation x² – bx + c = 0 be 1, then
(a) b² – 4c + 1 = 0
(b) b² + 4c = 0
(c) b² – 4c – 1 – 0
(d) b² – 4c = 0

Answer/Explanation

Answer: c
Explaination:
Let roots are α and β
⇒ α – β = 1
∵ (α – β)² = (α + β)² – 4αβ
⇒ 1 = b² – 4c
⇒ b² – 4c – 1 = 0


40. If α + β = 4 and α3 + β3 = 44, then a, p are the roots of the equation
(a) 2x² – 7x – 7 = 0
(b) 3x² + 8x + 12 = 0
(c) 3x² – 12x + 5 = 0
(d) none of these

Answer/Explanation

Answer: d
Explaination:
α3 + β3 = (α + β)3 – 3αβ(α + β)
⇒ 44 = (4)3 – 3αβ × 4
⇒ 44 – 64 = – 12 αβ
⇒ αβ \(=\frac{20}{12}=\frac{5}{3}\)
∴ quadratic equation is
x² – (α + β)x + αβ = 0
⇒ x² – 4x + \(\frac{5}{3}\) = 0
⇒ 3x² – 12x + 5 = 0


41. If the roots of equation 3x² + 2x + (p + 2)(p – 1) = 0 are of opposite sign then which of the following cannot be the value of p?
(a) 0
(b) – 1
(c) \(\frac{1}{2}\)
(d) – 3

Answer/Explanation

Answer: d
Explaination:
∵ roots are of opposite sign
∴ product of the roots is negative
⇒ (p + 2)(p – 1) should be negative.
Clearly when p = – 3, (p + 2) (p – 1) is not negative.


42. The value of k for which the equation x² + 2(k + 1)x + k² = 0 has equal roots is
(a) – 1
(b) –\(\frac{1}{2}\)
(c) 1
(d) none of these

Answer/Explanation

Answer: b
Explaination:
For equal roots, D = 0
⇒ [2(k+ 1)]² – 4 × k²=0
⇒ 4(k + 1)² – 4k² =0
⇒ 4(k² + 2k + 1) – 4k² = 0
⇒ 8k + 4 = 0
⇒ k = \(\frac{-1}{2}\)


43. If the equation x² – (2 + m)x + (-m² – 4m – 4) = 0 has coincident roots, then
(a) m = 0, m = 1
(b) m = 2, m = 2
(c) m = -2, m = -2
(d) m = 6, m = 1

Answer/Explanation

Answer: c
Explaination:
For coincident roots, D = 0
⇒ [-(2 + m)]² – 4 × 1 × (- m² – 4m – 4) = 0
⇒ (2 + m)² + 4(m² + 4m + 4) = 0
⇒ (2 + m)² + 4(m + 2)² = 0
⇒ 5(2 + m)² = 0
⇒ (2 + m)² = 0
⇒ m = -2.


44. If x = 2 is a solution of the equation x² – 5x + 6k = 0, the value of k is ______ .

Answer/Explanation

Answer:
Explaination:
Substituting x = 2, we have
(2)² – 5x² + 6k = 0
⇒ 4 – 10 + 6k = 0
⇒ k = 1


45. Check whether the following are quadratic equations:
(i) (x – 2) (x + 5) = (x – 3) (x + 4) + x²
(ii) x² – 3x + 5 = (x + 5)²
(iii) x3 – 3x² + 5x = (x – 2)3
(iv) (x – 7)x = 3X2 – 5
(v) (x² + 1) (x + 2) = (x + 3)²
(vi) (2x + 1) (x – 3) = (x – 1)²

Answer/Explanation

Answer:
Explaination:
(i) Given equation is (x – 2) (x + 5) = (x – 3)(x + 4) + x²
⇒ x² + 3x- 10 = x² + x- 12 + x²
⇒ x² – 2x – 2 = 0
which is of the form ax² + bx + c = 0
So, it is a quadratic equation.

(ii) Given equation is x² – 3x + 5 = (x + 5)²
⇒ x² – 3x + 5 = x² + 10x + 25
⇒ 13x + 20 = 0
which is not of the form ax² + bx+ c = 0
Hence, it is not a quadratic equation.

(iii) Here given equation is x3 – 3x² + 5x = (x – 2)3
⇒ x3 – 3x² + 5x = x3 – 6x² + 12x – 8
⇒ 3x² – 7x + 8 = 0
which is of the form ax² + bx + c = 0
Hence, given equation is a quadratic equation.

(iv) Given equation is (x – 7)x = 3x² – 5
⇒ x² – 7x = 3x² – 5
⇒ x² + 7x – 5 = 0
which of the form ax² + bx + c = 0
Hence, given equation is a quadratic equation.

(v) Given equation is
(x² + 1) (x + 2) = (x + 3)²
⇒ x3 + 2x² + x + 2 = x² + 6x + 9
⇒ x3 + x² – 5x – 7 = 0
It is of degree 3 and is not of the form ax² + bx + c = 0
Hence, given equation is not a quadratic equation.

(vi) (2x + 1) (x – 3) = (x – 1)²
⇒ 2x² – 6x + x – 3 = x² – 2x + 1
⇒ x² — 3x — 4 = 0
which is of the form ax2 + bx + c – 0
Hence, given equation is a quadratic equation.


46. Is x = -2 a solution of the equation x² – 2x + 8 = 0?

Answer/Explanation

Answer:
Explaination:
x² – 2x + 8 = 0
When x = – 2, LHS = (-2)² – 2(-2) + 8
= 4 + 4 + 8 = 16 ≠ 0
∴ x = – 2 is not a solution of the given equation.


47. If x = 3 is one root of the quadratic equation x² – 2kx -6 = 0, then find the value of k. [CBSE 2018]

Answer/Explanation

Answer:
Explaination:
Putting x = 3 in x² – 2kx – 6 = 0, we get
3² – 2k × 3 – 6 = 0
⇒ 9 – 6k – 6 = 0
⇒ 3 – 6k = 0
⇒ 3 = 6k
∴ k = \(\frac{3}{6}\) = \(\frac{1}{2}\)


48. Are x = 0, x = 1 the solution of the equation x² + x + 1 = 0?

Answer/Explanation

Answer:
Explaination:
Given equation is x² + x + 1 = 0
When x = 0, LHS = 0² + 0+ 1 = 1 ≠ 0
∴ x = 0 is not the solution.
When x = 1, LHS = 1² + 1 + 1= 3 ≠ 0
∴ x=1 is not the solution of given equation.


49. Ruchir was asked his age by his friend. Ruchir said “The number you get when you subtract 25 times my age from twice the square of my age will be thrice your age.. If the friend’s age is 14 years, then the age of Ruchir is_______ .

Answer/Explanation

Answer:
Explaination:
Let Ruchir’s age = x
A.T.Q. 2x² – 25x = 3 × 14
⇒ 2x² – 25x – 42 = 0
⇒ x = 14 years


50. The number of integral values of x so that 22x² – 7 + 5 = 1 is ______ .

Answer/Explanation

Answer:
Explaination:
22x² – 7x + 5 = 1
⇒ 2x² – 7x + 5 = 0
⇒ x = 1, \(\frac{5}{2}\)
∴ Integral value of x = 1.


51. Solve the following quadratic equation by factorisation: √3x² + 10x + 7√3 = 0.

Answer/Explanation

Answer:
Explaination:
√3x² + 10x + 7√3 = 0
⇒ √3 x² + 7x + 3x + 7√3 = 0
⇒ x (√3x + 7) + √3(√3x + 7) = 0
⇒ (√3x + 7)(x + √3) = 0
⇒ x = \(\frac{-7}{\sqrt{3}}\) or x = -√3


52. If p, q and r are rational numbers and p ≠ q ≠ r, then roots of the equation (p² – q²)x² – (q² – r²)x + (r² – p²) = 0 are

Answer/Explanation

Answer: d
Explaination:
Putting x = – 1, we have
(p² – q²)(-1)² – (q² – r²)(-1) + (r² – p²)
⇒ p² – q² + q² – r² + r² – p² = 0
∴ x = – 1 is one root. Only option (d) has one root – 1.


53. If α, β are roots of x² + 5x + a = 0 and 2α + 5β = -1, then a is equal to.

Answer/Explanation

Answer: d
Explaination:
Here α + β = -5 …(i)
and 2α + 5β = -1 …(ii)
Multiplying (i) by 2, we get
⇒ 2α + 2β = – 10 …(iii)
Solving (ii) and (iii), we get α = -8, β = 3
Now αβ = \(\frac{a}{1}\)
⇒ a = -24


54. α, β are roots of the equation (a + 1 )x² + (2a + 3)x + (3a + 4) = 0. If α . β = 2, then α + β =

Answer/Explanation

Answer:
Explaination:


55. If the roots of the equation 12x² + mx + 5 = 0 are in the ratio 3 : 2, then m equals______ .

Answer/Explanation

Answer:
Explaination:
Let roots are 3x and 2x.
Sum of roots = 3x + 2x = 5x = \(\frac{-m}{12}\)
⇒ x = \(\frac{-m}{60}\) ……(i)
Product of roots = 3x.2x = 6x² = \(\frac{5}{12}\)
⇒ x² = \(\frac{5}{72}\) ……(ii)
From (i) and (ii), \(\frac{m²}{3600}\) = \(\frac{5}{12}\)
m² = 5 × 50
m² = 5 × 5 × 10
m = 5√10


56. For what value of k. the roots of the equation x² + 4x + k = 0 are real? [Delhi 2019]

Answer/Explanation

Answer:
Explaination:
D = b² – 4ac
⇒ D = (4)² – 4 × 1 × k
⇒ D = 16 – 4k
For real roots, D ≥ 0
⇒ 16 -4k ≥ 0
⇒ 16 ≥ 4k
⇒ k ≤ 4


57. Write the nature of roots of quadratic equation 4x² + 4√3x + 3 = 0.

Answer/Explanation

Answer:
Explaination:
Given equation is 4x² + 4√3x + 3 = 0,
Here a = 4, b = 4√3, c = 3
D = b² – Aac = 48 – 48 = 0
As D = 0, the equation has real and equal roots.


58. Write the nature of roots of quadratic equation : 4x² + 6x + 3 = 0

Answer/Explanation

Answer:
Explaination:
Given quadratic equation is 4c² + 6x + 3 = 0.
Here, a = 4, b = 6, c = 3
D = b² – 4ac
⇒ D = (6)² – 4 × 4 × 3
= 36 – 48 = -12 < 0
∴ Given quadratic equation has no real roots.


59. If arithmetic mean of two numbers a and b is 8 and ab = 9, find a quadratic equation whose roots are a and b.

Answer/Explanation

Answer:
Explaination:
Here \(\frac{a+b}{2}\)= 8
⇒ a + 6 = 16 and ab = 9
Now, quadratic equation whose roots are a and b is
x² – (a + b)x + ab = 0
⇒ x² – 16x + 9 = 0


60. If 2x² – (2 + k)x + k = 0 where k is a real number, find the roots of the equation.

Answer/Explanation

Answer:
Explaination:
Given quadratic equation is 2x² – (2 + k)x + k = 0.
Here, a = 2, b = -(2 + k), c = k
Now, a + b + c = 2 + [-(2 + k)] + k = 0
∴ roots are 1 and \(\frac{k}{2}\).
(If a + b + c = 0, then roots of the quadratic equation are 1 and \(\frac{c}{a}\))


We hope the given MCQ Questions for Class 10 Maths Quadratic Equations with Answers will help you. If you have any query regarding CBSE Class 10 Maths Chapter 4 Quadratic Equations Multiple Choice Questions with Answers, drop a comment below and we will get back to you at the earliest.

Kishen

Recent Posts

Download CA Foundation Books PDF | Subjectwise CA Foundation Books for Preparation

CA Foundation Books: Institute of Chartered Accountants of India releases the books for ICAI. Refer…

7 days ago

NCERT Solutions for Class 8 Maths Term 1 and Term 2 [Updated 2021-22]

Here we are providing NCERT Solutions for Class 8 Maths, the solutions are latest and up-to-date.…

7 days ago

Chapter-wise MCQ Questions for Class 10 Social Science with Answers PDF Download

All Chapters MCQ Questions for Class 10 Social Science with Answers are prevailing here for…

3 weeks ago

Everything about Course Details | Stream Wise & Category Wise Courses

If you are looking for several courses that you can opt after your primary school…

3 weeks ago

How To Become An Astronaut In India? | Eligibility And Qualification, Advantages and Disadvantages

How To Become An Astronaut In India?: In childhood, almost all of us have dreamt…

3 weeks ago

How To Become An Entrepreneur In India? | Characteristics, Courses And Duration

How To Become An Entrepreneur In India?: "Business "is a highly fantasizing word that is…

3 weeks ago